A high Mn(II)-tolerance strain, Bacillus thuringiensis HM7, isolated from manganese ore and its biosorption characteristics - Huang,Huimin; Zhao,Yunlin; Xu,Zhenggang; Ding,Yi; Zhou,Xiaomei; Dong,Meng (PeerJ, 2020)
Microorganisms play a significant part in detoxifying and immobilizing excessive metals. The present research isolated a strain (HM7) with high Mn(II) tolerance from Mn(II)-contaminated soil samples. The 16S rDNA sequence analysis showed that HM7 had a 99% similarity to Bacillus thuringiensis, which can survive under a high concentration 4,000 mg/L of Mn(II), and the highest removal rate was up to 95.04% at the concentration of 400 mg/L. The highest Mn(II) removal rate was detected at the contact time 72 h, temperature 30 °C, and pH 5.0, while the differences in strain growth and Mn(II) removal rate among different inoculation doses were insignificant. Scanning electron microscopy indicated B. thuringiensis HM7 cells appeared irregular and cracked under Mn(II) stress. Fourier transform infrared exhibited that functional groups like carboxyl, hydroxyl, amino, sulfhydryl groups, and amide bands might take part in the complexation of Mn(II). In addition, HM7 suggested the ability of indoleacetic acid production, siderophore production, and P’ solubilization potential. Therefore, HM7 might have a potential to promote metal absorption by changing the form of heavy metals, and the experiments supported the application of B. thuringiensis HM7 as a biological adsorbent in Mn(II) contaminated environment remediation.
Keywords: Biosorption; Manganese removal efficiency; Promoting potential; Bacillus thuringiensis